Was 70 CE a watershed in Jewish history? : on Jews and Judaism before and after the destruction of the Second Temple - Schwartz, Daniel R.; Weiss, Zeev, 1959- (Ancient Judaism and early Christianity, 2012)
These twenty studies ask whether changes in different fields of ancient Jewish culture were caused by the destruction of the Second Temple in 70 CE, what changed for other reasons, and what did not change despite that event.